The Effectiveness of Pandan Wangi Leaves (Pandanus Amaryllifolius Roxb.)Body Scrub Formulation in Smoothing the Skin - L, Leny; Diana, Vivi Eulis; Ginting, Mandike; Iskandar, Benni; Fadhila, Cahya (Asian Journal of Pharmaceutical Research and Development, 2022)
This study aims to formulate ethanol extract of pandan wangi leaves into a cream body scrub preparation and examining the effectiveness of body scrub in smoothing the skin by analyzing the moisture and evenness of volunteers' skin. This research was carried out by sample processing, extract making, formulating cream body scrub preparation by evaluating its consistency, color and odor (organoleptic), homogeneity, pH of preparation, spreadability, emulsion type, irritation test, stability and effectiveness test using skin analyzer. Cream scrub preparations were made with several concentrations, namely 1%, 2% and 3%. The results of the study showed that the ethanol extract of pandan wangi leaves (Pandanus amaryllifolius Roxb.) could be formulated in cream scrub preparations which show homogeneous preparations, pH ranging from 5.4-6.0, met the requirements for spreadability, was an oil in water emulsion type, did not irritate the skin and the preparations were stable during the accelerated stability test with cycling test method. Furthermore, the cream scrub preparations of Pandan wangi leaf extract can increase moisture and improve skin smoothness until 31.48% and show a significant different with another group test (p<0.05).